2014
DOI: 10.1111/exd.12488
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of skin and hair regeneration after wounding

Abstract: Skin wound healing is a complex regenerative phenomenon that can result in hair follicle neogenesis. Skin regeneration requires significant contribution from the immune system and involves substantial remodeling of both epidermal and dermal compartments. In this viewpoint, we consider epigenetic regulation of reepithelialization, dermal restructuring and hair neogenesis. Because little is known about the epigenetic control of these events, we have drawn upon recent epigenetic mapping and functional studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…This provides an opportunity for future broader clinical implementation of epigenetic targeting drugs for wound healing and treatment of skin disease. Thus, manipulating levels of histone modifications in adult tissue SCs in vivo for possible control of tissue regeneration is an important and timely endeavour . Furthermore, skin is a valuable model to study the behaviour of adult SCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides an opportunity for future broader clinical implementation of epigenetic targeting drugs for wound healing and treatment of skin disease. Thus, manipulating levels of histone modifications in adult tissue SCs in vivo for possible control of tissue regeneration is an important and timely endeavour . Furthermore, skin is a valuable model to study the behaviour of adult SCs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro scratch assays of cultured keratinocyte revealed that JMJD3 interacts with NF‐κB to demethylate H3K27me3 at the promoter of inflammatory, matrix metalloproteinase and growth factor genes . Interestingly, basal cell migration to the wounds resembles malignant cancer formation, which occurs by epithelial–mesenchymal transition (EMT) . One of the well‐known EMT regulators Slug/Snail2 was shown to be upregulated in the wounded skin .…”
Section: Epigenetic Reprogramming During Injury‐induced Epidermis Regmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial-mesenchymal transition (EMT) is a recent reported process through which epithelial cells lose some of their innate characteristics (cell polarity and cell-cell adhesion) and are endowed with migratory and invasive properties becoming mesenchymal stem cells 15 . Wound healing has remarkable similarities to cancer in EMT induction 16 . During wound re-epithelialization epidermal keratinocytes, acquire migratory phenotypes 17 .…”
Section: Linking Inflammation To Tumorigenesismentioning
confidence: 99%
“…Wound‐induced regeneration is thought to be controlled by a complex signalling and epigenetic mechanism . In this issue, Garza's and Tumbar's groups discuss the roles of non‐coding double‐stranded RNAs and epigenetic reprogramming, respectively, in enabling such regenerative behaviour.…”
Section: Skin Morphogenesis Across the Regenerative Levelmentioning
confidence: 99%